THE INDIVIDUAL APPROACH TO IMPROVING THE MAIN COMPONENTS OF WOMEN'S PHYSICAL FITNESS - Natalia Grudnitskaya; Tatiana Mazakova (Вестник Северо-Кавказского федерального университета, 2022)
The article reveals the methodical sequence of individual fitness programs ' planning. These programs are aimed at the improving of women's physical fitness results and consist of the health fitness' complex: group sports exercises of different aerobics ' types and sports in the gym. The conducted pedagogical research confirms the effectiveness of the developed programs, which are constructed individually for each woman according to her level of physical condition.